850 Addressing Fertility Preservation in Patients Under the Age of 35 Diagnosed with Breast Cancer. A Ten-Year Audit in A Regional Unit. (12th October 2021) - Croitoru, C; Irwin, G
Abstract: Aim: In Northern Ireland, the incidence of breast cancer is 1, 443 cases per year with 26 patients diagnosed under the age of 35; 13% increase in 5 years. The average age of first-time mothers has increased from 24 to 28.8 in 2 decades. According to European Society of Medical Oncology, young patients should be counselled on available fertility preserving options before starting cancer treatment. Method: We have conducted a retrospective audit reviewing the management of breast cancer patients under the age of 35 in the Belfast Health and Social Care Trust, with a focus on fertility counselling and patient's options. Data obtained from Cancer Patient Pathway System and Patients records. Results: From July 2010 to July 2020 there were 92 patients diagnosed with breast cancer in the region. All patients are female, youngest 24 years old. 34 patients have been referred as 'Red Flag', 22 upgraded to 'Red Flag', rest as routine. 23 patients received neo-adjuvant chemotherapy as first line treatment, 68 underwent surgery in the first instance, one patient opted for private sector. Over 50% of patients had at least one child prior to referral. Less than 5% had considered pregnancy post or during treatment. Conclusions: At present there are no established guidelines regarding the timing of conception after diagnosis and treatment. Several options do exist for fertility preservation, both standard and investigational. There is evidence of an increasing recognition of this as a priority for patients and need early education and referral to fertility services for this emerging demographic.